Analysis of caesarean sections at a tertiary care centre according to Robson’s criteria - Mohapatra, Ipsita; Samantaray, Subha Ranjan; Vivekanand, Achanta; Manjula, Anandala; Priyanka, Buyyani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: There has been a considerable increase in the rate of caesarean sections in the past few decades. Some demographers have argued that this increase is largely affected by the uprising trend of new medically indicated caesarean sections. M. S. Robson proposed a ten-group classification of caesarean sections in year 2001 which was appreciated by WHO in 2014 and FIGO in 2016. This classification is known as Robson’s classification which has ten groups. Methods: This is a retrospective study which was carried out at Civil Hospital, Karimnagar. The study group included all live births and still births of at least 500 gm birth weight or at least 28 weeks of gestation at Civil Hospital, Karimnagar during the period from October 2019 to December 2019. The data collected was analysed using simple statistical methods like percentage and proportion. The data was grouped according to the Robson’s 10 group classification system. The overall caesarean section rate, size of each group and the relative contribution of each group to the overall CS rate were calculated. Results: The total number of deliveries during the study period was 2493. Out of these, the number of caesarean deliveries was 1345. The caesarean section rate was calculated to be 53.95%. The group 5 (multiparous with at least one previous uterine scar with single cephalic pregnancy ≥37 weeks of gestation) contributed to 38.07% of the total caesarean section rate which is the highest. Conclusions: A regular audit into the number and indications of caesarean sections will definitely help in decreasing the primary and repeat caesarean sections.